(untitled) (EU and comparative law issues and challenges series (ECLIC), 2018)
In contemporary criminal procedure, trial in absentia is considered an exception to the general principle that that a person charged with a criminal offence is entitled to take part at the hearing. The case law of the European Court of Human Rights defined several rules on trial in absentia, as prerequisites of compliance with fair trial standards from Article 6 of the European Convention on Human Rights and Fundamental Freedoms (ECHR). One of those rules concerns the possibility of retrial. Recently Croatia was condemned before in Sanader case, for violation of the right to a fair trial proclaimed in Article 6 ECHR, for the applicant’s inability to obtain a rehearing after conviction in absentia, without prior surrendering to custody based on that conviction. The execution of Sanader judgment included legislative amendments, which were adopted in July 2017. The paper analyses to what extent the present regulation of reopening of proceedings in cases of trial in absentia in Croatian legislation and practice corresponds to the European legal standards. The paper contains theoretical and normative analysis, as well as the research of the jurisprudence of the European Court of Human Rights and of recent jurisprudence of the Supreme Court of the Republic of Croatia. It showed that in Croatian judicial practice there are doubts on the purpose of reopening of proceedings in case of trial in absentia, which should provide “a fresh determination of the merits of the charge” by a court” in “full respect of defence rights”. Finally, the paper contains recommendations for the improvement of Croatian legislation and practice of reopening of criminal proceedings in cases of trial in absentia, in order to fully comply with European legal standards.